Network resource pricing strategy based on SDN framework - Bin ZHUGE; Yihang QI; Hanwen FU; Weiming WANG (Dianxin kexue)
A network resource pricing strategy based on SDN framework was proposed to solve the problem of resource overload and network congestion caused by resource requests in the network.Firstly,the user’s needs and consumption patterns were analyzed,and the resource transaction model was determined.Secondly,combined with the spot consumption model and plan consumption,the reservation mechanism under the resource dynamic pricing strategy model was determined.Finally,according to the proposed resource pricing strategy,the resource price was simulated,the results show that by stimulating the user to reserve resources in advance and combining the trust degree and consumption habits of each user with corresponding preferential prices,it is possible to effectively avoid the users from obtaining network resources in a centralized manner.